Social Responsibility and Ethics: A 20 Year Retrospective - Baranauskas, Cecília; S. de Souza, Clarisse; Höök, Kristina; Belloti, Victoria; Almeida, Virgílio; O. Prates, Raquel; Candello, Heloísa (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2018: Anais Estendidos do XVII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2018)
It has been 20 years since we have organized the first edition of IHC in 1998. So much has changed regarding not only technology, but also how it is inserted in our society. During this time, technology and people´s interaction with it have become ubiquitous and part of our everyday lives mediating many (if not most) of our ordinary activities from communicating with other people, to work, entertainment and Government services. As professionals who generate technology, this change has also raised our awareness, concern and attitude towards the social responsibility and ethics involved with developing technology and its use by society. In this panel, we discuss how social responsibility and ethics have changed and what is our role, as professionals, going forward.